The comparison of the outcome offine needle aspiration biopsy and needle biopsy accompanied by transrectal prostate ultrasonography in the diagnosis of prostate carcinoma (Annals of Medical Research, 2021)
None
Keywords: s : Prostate carcinoma, transrectal ultrasonography, prostate biopcy.